Thoughts from North Queensland - Singer, John (LiNQ (Literature in North Queensland), 2016)
John Singer, a Scot by birth, travelled extensively. He was trained as an anthropologist and worked, for much of his life, with overseas aid projects in Southeast Asia. He retired in 1978, and came to live in Townsville. He died in 1986. The extracts published here are from an occasional journal which he kept, recording his ideas, thoughts and feelings about North Queensland. Edited by Alec McHoul.